Investigating the role of poultry and the impact of HPAI on livelihoods in Ghana - Mensah-Bonsu, Akwasi; Asare-Marfo, Dorene; Birol, Ekin; Roy, Devesh (International Food Policy Research Institute, 2009)
Ghana experienced three confirmed highly pathogenic avian influenza (HPAI) outbreaks in 2007. The virus was detected on commercial farms of different sizes in three regions: in the Tema area (Greater Accra region) at the end of April, in the Sunyani area (Brong Ahafo region) in May, and in the Ketu district (Volta region) in June. These outbreaks were successfully controlled by the Veterinary Services Directorate (VSD), and no outbreaks have been recorded in the country since. However, the VSD is in a state of high alert because the virus is still circulating in West Africa (Aning et al. 2008).